Study on Synchronization of Two Eccentric Rotors Driven by Hydraulic Motors in One Vibrating System - Tianxia Zhang; Bangchun Wen; Jian Fan (Shock and Vibration)
In this article the synchronization of two eccentric rotors driven by hydraulic motors (TERDHM) in one vibrating system is studied. The differential equations of TERDHM motion are derived, and the synchronous and stable rotating conditions of TERDHM are established. It is found from the analysis and simulation that the angular velocities of TERDHM act on each other and both vary in a small range approaching their mean value. The synchronous rotation speed is equal to the average angular velocity of TERDHM, and the phase difference between them depends on the difference of the flow rates of the two hydraulic motors.